(untitled) (Bangladesh Journal of Microbiology, 2024)
Antibiotic resistance among various microbial species is becoming a global threat to human health. MDR, or multidrug resistance, is an organism’s ability to tolerate the effects of many antimicrobial treatments. Klebsiella spp. is the major bacteria that causes a variety of illnesses, including urinary tract infections. The primary goal of this study is to look into the relationship between antibiotic resistance and Klebsiella spp. biofilm production. This study included 26 clinical isolates of Klebsiella spp. (n=26) collected from a tertiary hospital in Bangladesh. Isolates were obtained from blood, wound swabs, urine, and other sources. Following isolation and identification, ampicillin resistance was found in all MDR Klebsiella spp. isolates, followed by Cefotaxime (84.61%), Polymyxin B (84.61%), Amoxicillin (80.76%), Trimethoprim (69.23%), Doripenem (57.69%), Ciprofloxacin (57.69%), Imipenem (50.0%), Meropenem (38.46%), and Oxytetracycline (34.61%). Out of 26 clinical isolates, about 26.92% (n=7) were positive for the bla-NDM-1 gene. However, 15.8% of Klebsiella spp. (n = 4) isolates tested positive for the blaOXA-1 gene. There were no bla-KPC gene positives. Plasmid profile analysis revealed that 24 of 26 Klebsiella spp. isolates included numerous plasmids ranging in size from less than 2kb to more than 10kb. Biofilm formation found that 31% of samples were extremely positive for biofilm formation, 69% were medium biofilm formation, and (n=4) isolates were positive for biofilm resistance gene out of a total of 26 isolates. This study provides an early report on the widespread presence of carbapenem-resistant Klebsiella spp., demonstrating the need for intensive surveillance systems and research initiatives in Bangladesh to reflect the influence of multidrug resistance features in clinical isolates and their risks. Bangladesh J Microbiol, Volume 40, Number 1, June 2023, pp 25-32